Interactive learning on building a negative voltage generator - Lee, Yi Xuan (Nanyang Technological University, 2023)
As e-learning grows to be an increasingly popular option for students, the role of digital tools in education has become welcomed and relied upon one. Additionally, as the COVID-19 pandemic further fuels the industry, the ability to provide a quality e-learning experience has become extremely valuable. This project, Interactive Learning on Building a Negative Voltage Generator (NVG), aims to create an e-learning platform from scratch that allows students to learn the topic of building a NVG at their own pace through the curated content. Specifically, the multimedia content and hands-on activities, including a hardware experiment, have been curated to enhance students’ learning. Ultimately, this project serves to allow students to engage in their learning at their own pace and desired location for their own convenience and improved learning. The project also assumes a blended learning approach where students are encouraged to contact the professor in charge for further clarifications and learning offline, instead of purely relying on the e-learning material provided. The report showcases the software and hardware development of the project, showing how the e-learning platform has been developed using the Software Development Life Cycle Model and later implemented by deploying code to a local server.